Hotel Service Quality in Jakarta, Indonesia - Hidayat, Candra; Darsiah, Anis; Nofiyanti, Fifi (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to explore customer perceptions of service quality in star-rated hotels in Jakarta, Indonesia. Given the increasingly fierce competition in the hospitality industry and the increasing demands of customers, an in-depth understanding of customer experiences and expectations is essential. The approach used was qualitative with in-depth interviews with 12 purposively selected informants, accompanied by triangulation analysis of data through bold customer reviews. The results showed that five dimensions of service quality based on the SERVQUAL model efficiency, responsiveness, assurance, empathy, and tangibles emerged as the main themes. Customers emphasized the importance of service, staff response speed, sense of security during stay, personal attention, and the comfort of the hotel's physical environment. Customer segmentation showed that business and leisure preferences had different focuses in assessing service quality. The conclusion of this study is that effective service quality includes both functional and emotional aspects in customer interactions. It is recommended that hotel management improve staff training, personalize services, and optimize digital systems to respond to customer needs in real time. This study contributes to the development of hotel service improvement strategies in metropolitan cities.